Genetic profile analysis of tumor stem cells in locally advanced breast cancer - Silveira, Willian Abraham da (2015)
INTRODUCTION: Breast cancer is the most common cancer in women worldwide and metastatic dissemination is the principal factor related to death by this disease. Breast cancer stem cells (bCSC), defined in this work as the ALDH1high/LIN-/ESA+ population, are thought to be responsible for metastasis and chemoresistance. The objective of this work is to find gene master regulators, in particular transcription factors (TFs), which are controlling the bCSC phenotype. METHODS: We used in this work two groups of datasets with transcriptome data, the discovery dataset group contains one dataset obtained by ourselves containing three paired samples comparing the bCSC and the bulk of the tumor (My Data - bCSC/Bulk dataset), a dataset with eight paired samples comparing the bCSC and cancer cells (Wicha - bCSC/CC dataset) and a dataset with 115 samples of breast cancer tissue (clinical response dataset). The second group, validation datasets, contains the BRCA-TCGA dataset with information of 621 samples, 4142 breast cancer samples of the Kmplot tool, 17 primary samples of BasL subtype and their information of grafting in patient derived xenografts and analyzes of cell lines (MF10A and HMLE). For the analyzes we used the paired t-test in the Limma R package, the ARACNE algorithm for the inference of regulons in the clinical response dataset, MRA-FET to define the master regulators of the bCSC phenotype, and GSEA to identify the biological meaning of the findings in the different datasets. RESULTS: We identified 12 TFs as master regulators of the bCSC phenotype, with nine of them forming two highly interconnected networks, one positively related with the bCSC phenotype formed by SNAI2, TWIST, PRRX1, BNC2 and TBX5 with its regulons, defined here as the mesenchymal transcription network and one negative correlated to the phenotype formed by SCML4, ZNF831, SP140 and IKZF3, defined as the immune response transcription network, totally unknown in the context of breast cancer in the literature. Although still with weak evidence, ZEB1 seems to control the two networks and can be responsible for the expression of ALDH1 and of the three remaining TFs: ID4, HOXA5 and TEAD1. As their names portray, our data showed in the different datasets, and independently of the molecular subtype and of the platform used, that the mesenchymal transcription network seems to be responsible for the bCSC phenotype and the immune response transcription network to the adaptive immune response in the tumor and a better prognosis for the patients. We also defined 10 membrane proteins as new markers and/or therapeutic targets of the bCSC. CONCLUSION: We found and described two TF networks that seem to control the bCSC phenotype, one of them totally unknown until now and correlated to a good prognosis. Our findings have a clear potential for clinical use.